PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPSKELAS VII SEMESTER GENAP DI SMP NEGERI 3 PANJI KABUPATEN SITUBONDO - Miftahus Surur; Lutfiya Jamil (STKIP PGRI SITUBONDO, 2018)
Teaching and learning activities in schools are the most fundamental activities. This means that successful there is no quality education among customers on how the learning process is experienced by students. The process for teaching and learning to run smoothly is done by the teacher, namely by increasing learning motivation. Motivation to learn is a conscious effort to direct and maintain the safety of a person's behavior so that he is motivated to act to do something so as to achieve certain results or goals. Intrinsic motivation is the motivation to learn that comes from the students themselves. If students have intrinsic motivation within themselves, then they will consciously carry out an activity that does not require external motivation. Interest has a huge influence on the course of the student process. If students are interested in learning a lesson or something it will work out well.